Synthesis and characterization of karaya gum-g- poly (acrylic acid) hydrogels and in vitro release of hydrophobic quercetin - Bashir, Shahid; Teo, Yin Yin; Ramesh, Subramaniam; Ramesh, Kasi (Elsevier, 2018)
Interest in the development of new materials based on natural polysaccharides has grown exponentially in the last decade. Therefore, polysaccharide hydrogels gain striking attention having unique properties. In this study, karaya gum polysaccharide hydrogels have been synthesized using free radical mechanism. In this mechanism, ammonium persulfate (APS) was used as an initiator to form free radicals of karaya gum and acrylic acid while N, N′-methylenebisacrylamide (MBA) was used to crosslink these radicals. The synthesized hydrogels were characterized in terms of structure and properties. The structural evaluation was performed using different techniques. The vanishing of existing and appearance of new functional groups were analyzed using Fourier transform infrared (FTIR) analysis. The physical state of the hydrogel was evaluated using X-ray diffraction analysis while thermal stability and formation of hydrogels were further confirmed using Differential scanning calorimetry (DSC). The morphology study was conducted using Field emission scanning electron microscope (FESEM). Furthermore, mechanical properties of hydrogels were investigated using rheometer and swelling properties were evaluated in water and buffer solutions of pH 7.4 and pH 1.2. Hydrophobic drug loading and structural stability of drug after drug loading are the major challenges in the drug delivery. Hydrophobic drug quercetin was loaded, and in vitro release studies were conducted. The quercetin release showed complete non-Fickian transport mechanism. All these results revealed the successful synthesis of hydrogels and potential applications of hydrogels in hydrophobic drug delivery.